Human-Centered AI and the Future of Translation Technologies: What Professionals Think About Control and Autonomy in the AI Era - Miguel A. Jiménez-Crespo (Information)
Two key pillars of human-centered AI (HCAI) approaches are “control” and “autonomy”. To date, little is known about professional translators’ attitudes towards these concepts in the AI era. This paper explores this issue through a survey study of US-based professional translators in mid-2024. Methodologically, this paper presents a qualitative analysis of open-ended questions through thematic coding to identify themes related to (1) present conceptualizations of control and autonomy over translation technologies, (2) future attitudes towards control and autonomy in the AI era, (3) main threats and challenges, and (4) recommendations to developers to enhance perceptions of control and autonomy. The results show that professionals perceive control and autonomy differently in both the present and the future. The main themes are usability, the ability to turn on and off technologies or reject jobs that require specific technologies, collaboration with developers, and differences in working with LSPs versus private clients. In terms of future attitudes, the most frequent ones are post-editing, quality, communicating or informing clients, LSPs or society at large, and creativity or rates. Overall, the study helps identify how professionals conceptualize control and autonomy and what specific issues could help foster the development of truly human-centered AI in the translation profession.